The evaluation of children referred for health measure ruling according to the Child Protection Law - Saday Duman, Nagihan; Sari Gokten, Emel; Efe, Aysegul; Buyukuysal, Cagatay (The European Research Journal, 2016)
Objective. To assess the children referred to our clinic with a health measure ruling which was given in accordance with Turkey’s no. 5395 Child Protection Law, in terms of socio-demographic characteristics, psychiatric diagnosis, and follow-up.Methods. Thirty children referred to our clinic with a health measure ruling given according to Turkey’s no. 5395 Child Protection Law were assessed.Results. The mean age was 13.20±3.86 (min-max: 2-17). Referral reasons of the children with a health measure ruling included driven to crime in 7 (23.3%), family therapy in 8 (26.7%), sexual abuse in 8 (26.7%), substance abuse in 3 (10%), physical abuse in 1 (3.3%), and medical care and rehabilitation in 3 (10%) children. Of the children referred for a health measure, 19 (63.3%) did not continue following the initial assessment.Conclusions. To enhance the effectiveness of the protective and preventive mental health services, children and adolescents who have a health measure ruling should be treated, followed-up, and rehabilitated at every stage of the process. It is necessary to increase in-house and inter-agency communication in order to implement the system effectively for the benefit of these children.